Tradition and Innovation Dialectics in Russian Dissertation Culture - P. I. Kasatkin; E. A. Antyukhova (Vestnik MGIMO-Universiteta)
Today in Russia the system of the state scientific certification undergoes significant changes: the powers of federal executive authorities are delegated to the educational and scientific organizations. As a result, independence in the choice of mechanisms, orders and procedures of formation of dissertation committees and criteria of awarding academic degrees is allowed. At the same time reinterpretation of axiological bases of dissertation culture through overcoming the problems connected with authenticity and quality of dissertation researches, by increase in reputation responsibility of the organizations and scientists takes place. On May 31, 2019 it will be a year to the moment of transition of the MGIMO University to a new model of the state scientific certification. According to the model developed by the MGIMO University, awarding an academic degree comes by the results of the defense of a thesis at a meeting of the dissertation committee of 5 doctors of science, three of which are employees of the MGIMO University, and two are invited scientists from other organizations. Two of five are experts with publications in the scope of the research combining the role of a member of the dissertation committee and an official opponent. The result of the defense is politically variable: alongside with the possibility of taking the negative decision awarding an academic degree without completions of the text and also under the condition of insignificant and considerable completions of the text of a research is allowed. The lack of such opportunities in the practice of awarding academic degrees existing in the domestic dissertation culture excluding modification of the manuscript submitted to defence after holding a meeting of dissertation committees, as well as other defects of the historically developed model of awarding academic degrees, defined the fastest transition of the MGIMO University to a new model of certification. «MGIMO Review of International Relations» discussed the main milestones of formation and key problems of development of the domestic dissertation culture with P. Kasatkin and E. Antyukhova.